From institutional websites to social media and mobile applications - Ramos, Ricardo F. (2019)
Ramos, R. F., Rita, P., & Moro, S. (2019). From institutional websites to social media and mobile applications: A usability perspective. European Research on Management and Business Economics, 25(3), 138-143. https://doi.org/10.1016/j.iedeen.2019.07.001